Temporality and Memory in Architecture: Hagia Sophia - Nur, Yüksel Burçin; Say Özer, Yasemen (ICONARCH International Congress of Architecture and Planning, 2017)
Istanbul, having hosted many civilizations and cultures, has a long and important past. Due to its geopolitical locations, the city has been the capital of two civilizations—Ottoman and Byzantine Empires—which left their traces in the h world history. Architectural and symbolic monuments built by these civilizations made an impression in all communities making the city a center of attraction. After each and every damages caused by wars, civil strifes, and natural disasters, maximum effort has been made to restore these symbolic buildings. Society’s attitude toward to a piece of art or an architectural construction defined as historical artifact and is shown in interventions, architectural supplementations and restorations to buildings to keep them alive. As a result of this attitude, it is accepted that buildings are perceived as a place of memory and symbolized along with the city. The most important symbolic monument of the city, Ayasofya (Hagia Sophia), was founded as the Church of the Byzantine Emperor in the year 360, then converted into the Mosque of the Ottoman Sultan, and now serves as one of the best-known museums of Turkey. With architectural additions requested by Byzantine emperors and Ottoman sultans, restorations and other functional changes; Hagia Sophia had become a monument witnessing its own changes as well as its surroundings while collecting memories. Accordingly, Hagia Sophia can be described as an immortal building. Immortality is out of time notion, however it is a reflection of time effects as well. Immortality is about resisting to time. Any construction from the past which appreciates as time passes will also exist in the future preserving its value. The building has been strengthened with the memory phenomenon formed during construction, incidents that the building witnessed in its location, restorations, architectural supplementations and the perception of the world heritage. The main purpose of this presentation is to show how an intangible concept as memory concretizes in an architectural structure, within the context of immortality and time concepts, by examining Hagia Sophia.